The Relationship of Economic Growth, Export Value and Inflation with The Autoregressive Distributed Lag (ArDL) Approach - Fitriyanto, Nur (Universitas Dian Nuswantoro Semarang, 2023)
Economic growth is one of the benchmarks for the success of a country in running the economy along with the factors that influence it, so this is important to observe. Many previous studies have proven the influence of export value and inflation on economic growth. This study chooses the Autoregressive Distributed Lag (ARDL) model approach to see the dynamics of long-term and short-term relationships for the variables of export value, inflation and economic growth. The research period is quarterly, starting from 2011:Q1 – 2019:Q4 with the type of time series data. The results of this study, through the ARDL model, the variables of export value and inflation are proven to have long-term cointegration or move together in the long term towards economic growth. This study also succeeded in revealing that the variables of export value and inflation have a short-term relationship with a relatively fast adjustment time, which is 2-3 months to return to balance. Keywords:ArDL, export value, economics growth